Doświadczenie krajobrazu w pismach podróżniczych Dyzmy Bończy Tomaszewskiego - Bąkowska, Patrycja (Poznańskie Studia Polonistyczne. Seria Literacka, 2025)
This article focuses on selected travel writings by Dyzma Bończa Tomaszewski who, though little known for his poetic achievements, was remembered primarily as an opponent of the May 3rd Constitution of 1791. This stance notwithstanding, his work offers research material worthy of in-depth consideration, enabling us to trace the processes of aesthetic and literary transformation that occurred during the Polish Enlightenment. The issues raised in this analysis concern literary methods of representing landscape: motifs, strategies, and conventions employed to convey the “gaze of the viewing subject” as simultaneously observer but also co-creator of the seen landscape. Tomaszewski drew from, among other things, classical traditions, employing, for instance, the motif of Hercules at the crossroads. At the same time, he remained open to emerging literary trends and, more broadly, to the culture of the more mature later stages of the Age of Light.